Sunday

December 21, 2014

December 21, 2014

Posted by **Courtney** on Thursday, May 5, 2011 at 6:00pm.

An=6N-2

- Math -
**Reiny**, Thursday, May 5, 2011 at 6:05pmA(n) = 6n - 2

A(1) = 6(1) - 2 = 4

A(2) = 6(2) - 2 = 10

etc.

**Answer this Question**

**Related Questions**

precalculus - Find the first five terms of the given recursively defined ...

Advanced Functions - I need help answering these questions 1. State the Common ...

Math - Question 1 Write the first four terms of the sequence whose general term...

Math PLEASE HELP PLEASE PLEASE PLEASE - Question 1 Write the first four terms ...

Math - Find the first five terms of the sequence using the recursive rule: a1 = ...

Math - an = 3n - 1 Answer 2, 3, 4, 5 2, 5, 8, 11 -2, -5, -8, -11 4, 7, 10, 13 3...

calculus - A) How do you prove that if 0(<or=)x(<or=)10, then 0(<or=)...

Calculus - A) How do you prove that if 0(<or=)x(<or=)10, then 0(<or=)...

calculus - A) How do you prove that if 0(<or=)x(<or=)10, then 0(<or=)...

Math - 1. What are the next two terms of the following sequence? -3, 1, 5, 9... ...